On the Estimation of the Interannual Variability of the Ocean Surface Temperature in the Area of the Peruvian Upwelling - Martina-Vasquez Jimmy; Gordeeva Svetlana; Malinin Valerii (Russian Journal of Earth Sciences)
The interannual variability of the ocean surface temperature in the area of the Peruvian upwelling for the period 1980–2022 is considered according to the satellite archive GODAS (Global Ocean Data Assimilation System) using the methods of multivariate statistical analysis. Local foci of significant trends, for average annual Sea Surface Temperature (SST) values, were identified near the Peruvian offshore. Four regions (clusters) were obtained, which describe the variability of SST in front off Peru, which could be used to pretend to develop a prognostic oceanographic model. Furthermore, coincidences of temperature fluctuations were found between the first cluster and the region N3+4